2015
DOI: 10.1097/igc.0000000000000323
|View full text |Cite
|
Sign up to set email alerts
|

The Work Place Educational Climate in Gynecological Oncology Fellowships Across Europe: The Impact of Accreditation

Abstract: This study emphasizes the need for better feedback mechanisms and the importance of accreditation of centers for training in gynecological oncology to ensure training within higher quality clinical learning climates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
0
17
0
3
Order By: Relevance
“…Prediction of departments' learning climate performance should yield essential improvement insights. For example, Piek et al (2015) found the accreditation status of gynecology residency training programs and the years of training completed by residents were important predictors of learning climate. Other studies compared gender groups, specialties and type of hospital for differences in their overall learning climate (D-RECT) scores (van Vendeloo et al 2014;Amin et al 2016).…”
Section: Practice Pointsmentioning
confidence: 99%
“…Prediction of departments' learning climate performance should yield essential improvement insights. For example, Piek et al (2015) found the accreditation status of gynecology residency training programs and the years of training completed by residents were important predictors of learning climate. Other studies compared gender groups, specialties and type of hospital for differences in their overall learning climate (D-RECT) scores (van Vendeloo et al 2014;Amin et al 2016).…”
Section: Practice Pointsmentioning
confidence: 99%
“…Also according to Piek J et al [2], the educational climate between Western Europe countries and Eastern Europe countries did not differ significantly by region and is similar between Western or Eastern European countries. However, scores did differ by country income, with higher income countries having apparently better overall educational climates than middle-income European countries.…”
Section: Discussionmentioning
confidence: 99%
“…Structured training also provides a better training environment and more effective feedback, the need for which has previously been reported. 8 Objective structured assessment of training evaluations has shown moderate correlations between bench tests and performance in live animals (wet laboratory) and the operating room. 23 Procedure-based assessments have demonstrated high reliability in obstetrics and gynecology (O&G) and non-O&G trainees.…”
Section: Discussionmentioning
confidence: 99%
“…9 Accreditation ensures institutions to maintain a minimally prescribed set of standards, case load, infrastructural process, and organizational process to facilitate training needs, which in turn leads to a more affective training program providing better supervision, coaching, assessment, feedback, teamwork, and professional relationships. 8 It is also important for institutions, national GO organizations, and training program directors to institute mechanisms for monitoring the quality of GO training. A central European register for GO trainees is currently lacking, and implementation of this would facilitate the monitoring and evaluation of training as well as guide policy and support for training needs/skills.…”
Section: Discussionmentioning
confidence: 99%